Essays on Technological Change, Growth and Labor Market Outcomes - Ana Isabel Moura Frias de Oliveira (2022)
This dissertation focus on technological change and how it has impacted economic growth, income distribution, employment, and wages. The first essay explores an endogenous growth model with incumbent and entrant firms performing vertical and horizontal R&D, respectively. Firms face sectorspecific fixed-costs and specific R&D efficiency. We introduce two sets of shocks: a temporary productivity shock, and a permanent shock to R&D fixed-costs. We find that the transition paths after the first set of shocks mimics the behavior of US data in the variables of interest in a given period. The second set of shocks, which compares two R&D-policy strategies, has important policy implications. The second essay studies the gender wage gap impacts of technological change. We find that, although changes in the employment structure have favored women over time, the wage level and wage growth in occupations women are employed in, and are transitioning towards, have operated as countervailing forces against the gender wage gap narrowing. This essay is joint work with Anna Salomons and Matias Cortes. It is published in the Oxford Review of Economic Policy. The third essay investigates whether the evolution of occupational employment shares and occupation-specific wage rates explains firm-level labor share dynamics. We demonstrate that the dynamics of the Portuguese aggregate labor share between 2004 and 2019 are mostly driven by changes in firms' labor share, which rise due to positive growth in hourly wages, rather than value-added reallocation across the labor share distribution. We further show that changes in task group employment shares have limited effects on firm-level labor shares.